(untitled) (Nexus International Journal of Science and Education, 2024)
This study viewed the nitty-gritty of working student of secondary schools in Sto.Niño National High School, Tugbok District, Davao City. There were eight (8) working who participated in the study. This study made use of a phenomenological approach to extract the ideas from the student participants. The participants were purposely selected as representatives from the working students in the school. The virtual in-depth-interview was employed to gather some information as regards to their respective experiences. Using the thematic analysis, the following themes emerged as it relates to the experiences of the participants: the experiences of the working students were on their difficulty balancing work and school duties, economically underprivileged and aiming to finish studies. The coping mechanisms of the working students were: Managing time wisely, focusing on the current duties and staying healthy and energetic. The educational management insights drawn from the findings of the study were: Engage working students in flexible learning mode, Provide proper guidance and school support to working students and Encourage peer learning. The home economics teachers may be more receptive to the need of their students. Other considerations for working students may be crafted to give enough time and space for them. The teachers may be more sensitive to the needs and wants of their students. The students may be directed well by their classroom advisers and the guidance counsellor of the school. The teachers attention to each of the students in the classroom plays a significant value specifically to the working students that they may be given proper guidance and directions for them to complete their dreamed diploma and gain a better life in the future.